Conversion of Degradable Solid Waste into Alternative Energy using Local Wastes as a Binder, Case of Southwestern Ethiopia - Abreham Bekele Bayu; Ketema Beyecha Hundie (Program Pascasarjana Universitas Sriwijaya, 2020)
The objective of this research is to produce high quality of charcoal from the most known local wastes as a binder. The solid waste was collected from Bonga city and the production of charcoal briquette based on different binder preparation. The local wastes like sawdust and paper were used as a binder comparing with starch as a standard binder. Since the result obtained by using sawdust shows better burning time and less smoke comparing with using paper as a binder. The proximate analysis result obtained for degradable solid waste was its density, percentage of moisture, volatile matter, ash, fixed carbon, and caloric value of 16.73 kg/m3,17.81%, 67.56%,4.78%, 9.85% and 18.39MJ/kg respectively. In the same way, fuel briquette using sawdust as a binder was characterized for its density, percentage of porosity, weight index, shatter resistance, moisture content, volatile matter content, ash content, fixed carbon content, and caloric value which is 750.06Kg/m3,29.05%,92.38%,9.87%, 29.6%, 3.56%, 56.97% and 27.38 MJ/kg respectively. Using sawdust is better than using paper as a binder since the briquette produced by using sawdust as a binder shows less smoke and higher burning time. This shows that it is possible to convert solid wastes into fuel briquettes using local wastes as binders.